2008
DOI: 10.1200/jco.2008.18.0786
|View full text |Cite
|
Sign up to set email alerts
|

Wild-Type BRAF Is Required for Response to Panitumumab or Cetuximab in Metastatic Colorectal Cancer

Abstract: Purpose Cetuximab or panitumumab are effective in 10% to 20% unselected metastatic colorectal cancer (CRC) patients. KRAS mutations account for approximately 30% to 40% patients who are not responsive. The serine-threonine kinase BRAF is the principal effector of KRAS. We hypothesized that, in KRAS wild-type patients, BRAF mutations could have a predictive/prognostic value. Patients and Methods We retrospectively analyzed objective tumor responses, time to progression, overall survival (OS), and the mutational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

47
1,028
12
33

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,495 publications
(1,129 citation statements)
references
References 36 publications
47
1,028
12
33
Order By: Relevance
“…As regards BRAF mutations, even if evaluated in a small subgroup of patients, our findings are consistent with the most part of published studies which have validated BRAF mutations obtained from primary tumour specimens as a strong negative prognostic biomarker in metastatic CRC (Ahn et al, 2014), showing a more aggressive and chemo-refractory behavior compared to wild-type tumours (Tran et al, 2011). However it's interesting to observe that the percentages of BRAF mutations (2-4%) in all the included studies is lower than those reported in the literature (5-10%) (Sridhar et al, 2005;Di Nicolantonio et al, 2008), likely due to the clinical selection of patients included in such studies. Indeed, because of their peculiar metastatic spread, BRAF-mutated tumours are usually detected as an advanced disease, rarely candidate for liver surgery.…”
Section: Discussionsupporting
confidence: 89%
“…As regards BRAF mutations, even if evaluated in a small subgroup of patients, our findings are consistent with the most part of published studies which have validated BRAF mutations obtained from primary tumour specimens as a strong negative prognostic biomarker in metastatic CRC (Ahn et al, 2014), showing a more aggressive and chemo-refractory behavior compared to wild-type tumours (Tran et al, 2011). However it's interesting to observe that the percentages of BRAF mutations (2-4%) in all the included studies is lower than those reported in the literature (5-10%) (Sridhar et al, 2005;Di Nicolantonio et al, 2008), likely due to the clinical selection of patients included in such studies. Indeed, because of their peculiar metastatic spread, BRAF-mutated tumours are usually detected as an advanced disease, rarely candidate for liver surgery.…”
Section: Discussionsupporting
confidence: 89%
“…215 The results showed that none of the patients who experienced a response displayed BRAF mutations, whereas 11 of 79 (14%) nonresponders carried a BRAF V600E allele. 215 As BRAF mutations are mutually exclusive to EGFR and KRAS mutations, it is likely to be associated with lack of response to EGFR TKIs. 138 …”
Section: Braf Mutationmentioning
confidence: 94%
“…215 BRAF mutations are found in 1-3% of lung cancers, most of which are adenocarcinomas. 206,212 BRAF mutations are found in a mutually exclusive pattern with KRAS mutations, suggesting that these genetic events activate a set of common downstream effectors of transformation.…”
Section: Braf Mutationmentioning
confidence: 99%
“…14 In the case of colorectal carcinomas, BRAFV600E mutation positive patients have significantly shorter progression-free survival when compared with patients with tumors with BRAF wild-type and its presence is shown to impair the therapeutic effect of drugs such as cetuximab and panitumumab. 15 The recognition of BRAFV600E mutation and its prognostic value has led to accelerated attempts to utilize it as a target for cancer therapy. Briefly, recent drugs targeted against mutated BRAF (particularly in melanomas) have shown great promise in early clinical trials.…”
mentioning
confidence: 99%